PENGARUH STATUS SOSIAL EKONOMI DAN JENIS KELAMIN TERHADAP LITERASI KEUANGAN (STUDI EKSPERIMEN PADA PELAKU UMKM DI MADIUN) - Ahmadi, Herman; Nur Sulistyowati, Liliek (Widya Warta, 2019)
Financial intelligence is the key to one's success in managing finances. the application of correct financial management, is expected to be able to get maximum benefits from the money they have, bills that swell and the ability to pay low will cause bad credit. The phenomenon of high non-performing loans shows that the financial literacy of some people, especially SME is low.  The objectives of this study are (1) To examine the effect of Financial Literacy on SME in Madiun on high or low socio-economic status, (2) Test the influence of Financial Literacy on SME players in Madiun on male SME actors or female SME actors, (3) Test influences Financial Literacy in SME in Madiun for SME business men with high socioeconomic status compared to female SME with low economic social status, (4) Testing the influence of Financial Literacy on SME entrepreneurs in Madiun for SME Women with socioeconomic status high compared to male SME actors with low socioeconomic status. This study used an experiment 2x2 between subjects. Laboratory experiments namely Experiments were designed using two, namely: socio-economic status (High, low) and Gender (male, female).  Participants were SME in Madiun city with 50 business units in processed food production,experimental furniture samples using random sampling, to classify subjects into experimental groups or control groups. As a result there were significant differences between male and female financial literacy, there were influences significant between high social status and low social status on financial literacy, men have a higher average financial literacy compared to  women, men with high social  status  are  higher  than women with low social status  evidenced  by  (mean = 20,7368)   higher   than    the low  social  status (mean = 18.0833),  women with high social status are higher than male gender with  low  social  status  as  evidenced  by  men  having an  average  financial  literacy (mean=20.6154)higher than women(mean=18.0833).